Why is there still hepatitis C transmission in Australian prisons? A case report. Issue 1 (December 2017) - Harkness, Ben; Levy, Michael; Evans, Ruth; Wenke, Jillian
Abstract Background The ability to cure hepatitis C viral infection, with specific reference to the prisoner population and the prison environment, will be challenged, even if opiate replacement therapy is concurrently offered, and even if bleach is available. The missing elements, widely available in the community, are a regulated injecting equipment exchange and tattooing parlours. Case presentation We report a case of re-infection of hepatitis C in a prisoner treated with a direct-acting antiviral. What makes this case so remarkable is that it was entirely predictable and preventable. Conclusions Hepatitis C infection will continue to test both the strengths and the weaknesses in the relationship between health and corrective services in Australia. Nothing less than full implementation of all harm minimisation modalities will be necessary to eliminate the clinical and public health risks of hepatitis C infection, both in prison and by extension into the general community.